Fat grafting for breast cancer patients: From basic science to clinical studies. Issue 8 (August 2016) - Gennari, R.; Griguolo, G.; Dieci, M.V.; Guarneri, V.; Tavaniello, B.; Sibilio, A.; Conte, P.
Abstract: Fat grafting in the surgical treatment of breast cancer has become popular in a short period of time because of the rising expectations of good esthetic results by the patients as well as the simplicity of the technique; however, the oncological safety for breast cancer patients remains a matter of debate. The procedure raises many questions considering that recent in-vitro studies have shown that fat grafting could promote tumor recurrence through diverse mechanisms, or even facilitate distant metastasis. We present a review of the currently available experimental and clinical data in order to describe and discuss patient selection criteria following breast cancer surgery.